2021
DOI: 10.1016/j.apsb.2020.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol targets adenylyl cyclase-associated protein 1 to reduce macrophages-mediated inflammation and ameliorates high fat diet-induced metabolic syndrome in mice

Abstract: Metabolic syndrome is a clustering of metabolic disorder with unclear molecular mechanism. Increasing studies have found that the pathogenesis and progression of metabolic syndrome are closely related to inflammation. Here, we report celastrol, a traditional Chinese medicine, can improve high fat diet-induced metabolic syndrome through suppressing resistin-induced inflammation. Mechanistically, celastrol binds to adenylyl cyclase associated protein 1 (CAP1) and inhibits the interaction between CAP1 and resisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
2
26
0
2
Order By: Relevance
“…A waterfall effect will form through positive feedback, which in turn cause the release of toxic substances and destroy the functions of cells and tissues (19)(20)(21). Macrophages play an important role in the inflammatory response of sepsis; they are activated to express a large number of pro-inflammatory factors and further promote the inflammatory response of sepsis (22). Meanwhile, the phagocytosis and sterilization of macrophages could not be ignored when pathogens invaded, while the functions were inhibited in sepsis (23).…”
Section: Introductionmentioning
confidence: 99%
“…A waterfall effect will form through positive feedback, which in turn cause the release of toxic substances and destroy the functions of cells and tissues (19)(20)(21). Macrophages play an important role in the inflammatory response of sepsis; they are activated to express a large number of pro-inflammatory factors and further promote the inflammatory response of sepsis (22). Meanwhile, the phagocytosis and sterilization of macrophages could not be ignored when pathogens invaded, while the functions were inhibited in sepsis (23).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings demonstrated that celastrol was able to reduce both SARS-CoV-2 viral load and IL-6 production in two human cell lines, suggesting that this compound exerts anti-SARS-CoV-2 effects of clinical relevance to face the current pandemic. Several pharmacological applications of celastrol are associated with Covid-19 severity, including comorbidities such as obesity, diabetes, hypertension, and metabolic syndrome [95][96][97][98] , and pathological events such as non-homeostatic production of pro-inflammatory cytokines, thrombus generation, and formation of neutrophil extracellular traps [99][100][101] . Celastrol is currently under clinical trials to treat a variety of diseases, including different types of cancer, neurodegenerative disorders, and inflammatory conditions such as rheumatoid arthritis, psoriasis, and Crohn's disease [102][103][104][105][106] .…”
Section: Discussionmentioning
confidence: 99%
“…Brain leptin promoted hepatic lipid flux and reduced lipogenesis in the liver ( Hackl et al, 2019 ). Celastrol as a leptin sensitizer exhibited significant weight loss and food consumption reduction in HFD-obesity animals ( Wang et al, 2014 ; Liu et al, 2015 ; Ma et al, 2015 ; Zhang et al, 2017a ; Hu et al, 2017 ; Luo et al, 2017 ; Kyriakou et al, 2018 ; Pfuhlmann et al, 2018 ; Zhang et al, 2018 ; Feng et al, 2019a ; Zhao et al, 2019a ; Feng et al, 2019b ; Chellappa et al, 2019 ; Fang et al, 2019 ; Saito et al, 2019 ; Abu Bakar et al, 2020 ; Hu et al, 2020 ; Zhu C. et al, 2021 ; Zhu Y. et al, 2021 ; Hua et al, 2021 ; Ouyang et al, 2021 ; Yang et al, 2021 ) ( Table 1 ).…”
Section: Celastrol and Liver Diseasesmentioning
confidence: 99%
“…Numerous evidences supported that obesity is strongly associated with MAFLD development ( Fabbrini et al, 2010 ). The liver protective effect and molecular mechanism of celastrol on high fat diet (HFD) induced MAFLD animal models have been well-investigated ( Wang et al, 2014 ; Ma et al, 2015 ; Zhang et al, 2017a ; Hu et al, 2017 ; Luo et al, 2017 ; Kyriakou et al, 2018 ; Pfuhlmann et al, 2018 ; Zhang et al, 2018 ; Feng et al, 2019a ; Zhao et al, 2019a ; Feng et al, 2019b ; Chellappa et al, 2019 ; Fang et al, 2019 ; Abu Bakar et al, 2020 ; Hu et al, 2020 ; Zhu C. et al, 2021 ; Zhu Y. et al, 2021 ; Hua et al, 2021 ; Ouyang et al, 2021 ; Yang et al, 2021 ).…”
Section: Celastrol and Liver Diseasesmentioning
confidence: 99%
See 1 more Smart Citation